The dark side of mobile work during non-work hours: moderated mediation model of presenteeism through conservation of resources lens - Choi, Woo-Sung; Kang, Seung-Wan; Choi, Suk Bong (Frontiers in Public Health, 2024)
Owing to the development of Information and Communication Technology (ICT) and the inevitability of telecommuting in the COVID-19 environment, the boundary between working and non-working hours has become blurred. mWork, that is, ICT-based off-hour work, which has increased through the pandemic, affects employees' work attitudes, such as presenteeism.Hence, we designed a study to investigate the antecedents and mechanisms of employee presenteeism from the perspective of the conservation of resources theory. We supported our hypothesis using a sample of 325 Korean office workers obtained through three rounds of timedelay surveys. The results show that presenteeism is higher among employees with high mWork. In addition, employees' mWork increases sleep deprivation and presenteeism, and the exchange ideology of employees reinforces the positive effect of sleep deprivation on presenteeism. Additionally, the higher the level of exchange ideology, the stronger the mediating effect of mWork on presenteeism through sleep deprivation. This study verified the conservation of resources theory by identifying the mechanism by which mWork affects an employee's life, which in turn affects their work, and provides practical implications for managing productivity loss due to presenteeism.